2010
DOI: 10.1510/icvts.2010.247213
|View full text |Cite
|
Sign up to set email alerts
|

Poor awareness of symptoms of oesophageal cancer

Abstract: Oesophageal cancer presents as advanced disease; in the majority of patients the symptoms are present for many months prior to diagnosis. Dysphagia has been described as the key to an early diagnosis of oesophageal cancer. This study aims to assess the public perception of the importance of this symptom. Ninety-six patients completed a questionnaire. This evaluated patient understanding of symptoms of dysphagia compared to the finding of a breast lump, haemoptysis, chest pain and loss of weight concerning urge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 5 publications
1
18
0
1
Order By: Relevance
“…This is important as oesophagogastric cancer has not been well-publicised compared with other cancer campaigns 5. A regional study in 2010 showed that only 10% of the public had appreciated dysphagia as a possible symptom of oesophagogastric cancer 5. In contrast, 71% of patients would seek medical advice after discovering a breast lump 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is important as oesophagogastric cancer has not been well-publicised compared with other cancer campaigns 5. A regional study in 2010 showed that only 10% of the public had appreciated dysphagia as a possible symptom of oesophagogastric cancer 5. In contrast, 71% of patients would seek medical advice after discovering a breast lump 5.…”
Section: Discussionmentioning
confidence: 99%
“…A regional study in 2010 showed that only 10% of the public had appreciated dysphagia as a possible symptom of oesophagogastric cancer 5. In contrast, 71% of patients would seek medical advice after discovering a breast lump 5. Data from a previous BCOC pilot had shown an increase in oesophagogastric cancer symptom awareness 3.…”
Section: Discussionmentioning
confidence: 99%
“…In a study concerning lung cancer and chronic obstructive pulmonary disease (COPD), upregulated CAPS expression was detected in lung cancer and lung cancer with COPD groups when compared with the control group, indicating that CAPS may serve as a biomarker fora lung cancer diagnosis (16). Esophageal cancer is one of the most aggressive cancer types worldwide owing to a lack of early typical symptoms and effective non-invasive diagnostic methods (21). Despite the efforts to improve diagnostic methods and therapeutic approaches, the quality of life and overall survival time for patients with ESCC is far from satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, inability to eat properly can adversely affect the health through dehydration and malnutrition, and it can also affect the quality of life [3], [4]. Dysphagia is also the most common symptom of esophageal cancer, and its early detection is crucial for the successful prognosis [5].…”
Section: Introductionmentioning
confidence: 99%